“Efecto de microorganismos benéficos en el cultivo de tomate (lycopersicum esculentum L.) en la provincia de Lamas” - Vásquez Tipa, John Bryan (2014)
The tomato is considered the most important in the country vegetable, since they contain a lot of vitamins such as A, B, C, E and K, also very necessary for daily consumption, is widely used in varieties of soups, in industry and also has medicinal properties with a possible effect in the prevention of cancers of the prostate and bladder. The production of the crop is tomato is cultivated widely at the national and departmental level, but many farmers are unaware of proper management due to overuse of chemicals for its production. Is why this paper examines the performance and conduct of the tomato crop using organic products, the effect causing the beneficial microorganisms in favor of a good production and also to help the population to produce their healthy vegetables every day, avoiding the use of chemicals that are harmful for our health to the maximum.